Population, habitat characteristic, and modelling of Endangered Orchid, Paphiopedilum javanicum in Mt. Lawu, Java, Indonesia - Muh Arif Romadlon; Fatimah Azzhara; Gilang Dwi Nugroho; Ari Pitoyo (Society for Indonesian Biodiversity, 2021)
Abstract. Romadlon MA, Azzhara F, Nugroho GD, Pitoyo A. 2021. Population, habitat characteristic, and modelling of Endangered Orchid, Paphiopedilum javanicum in Mt. Lawu, Java, Indonesia. Biodiversitas 22: 1996-2004. Paphiopedilum javanicum (Reinw. ex Blume) Pfitzer or Java Paphiopedilum is an endangered orchid categorized as appendix I in CITES. In its natural habitat, forest fire, habitat fragmentation, and extreme poaching are considerably the prominent threats for the species. The study aims to assess the population distribution, the habitat characteristics and model the suitable habitat of P. javanicum in Mt Lawu, Java, Indonesia using Maxent (Maximum Entropy) modelling. Eighteen subpopulations of P. javanicum spread across the region with a total number of 103 individuals. The majority of the individuals are in the generative phase (93.81%) and the rest are in the vegetative phase (6.19%). In Mt Lawu, P. javanicum can be found at an elevation of 1,231-1,825 m asl. in a deep shady forest floor with a thick litter and canopy cover between 0-77.4%. The soil has pH between 7-7.1 with 21.7%-36.7% of moisture. The air temperature ranging between 21.8?-29.7?C, with humidity of 61%-78.5%. Based on the Maxent test, annual mean temperature, vegetation cover, type of land use, and elevation are the most influencing factor of P. javanicum distribution in Mt Lawu. The model identifies 6814.75 ha areas in Mt Lawu that are suitable for the species distribution. Lawu Purba, the biggest suitable area for P. javanicum habitat in the southern part of the mountain holds the remaining natural forests in the region. The result is expected to provide recommendations for determining priority areas in the conservation efforts for this threatened orchid.